Interactive Learning Through ‘Si Ito’ Comics: Promoting Sumatera’s Eco-Tourism and Education - Srikandi, Cut Novita; Biha, Muntasya - (Globish: An English-Indonesian Journal for English, Education, and Culture, 2025)
This research discusses an eco-friendly bilingual Ito comic integrated application aimed at promoting Sumatra tourism, emphasizing comedic content that can enhance foreign tourist visitation to locations in North Sumatra. Data was gathered from the 2022 publication of Ito Comic. This comic was produced by a researcher and her esteemed colleagues in the Ito Comic Team. This research seeks to promote tourism in North Sumatra while fostering entrepreneurship through the production of comic books that advocate for eco-friendly initiatives. This study was executed using qualitative research methods. Assessment of market prospects involving 86 females and 37 males aged 10 to 30 years. Data indicated that 33% of respondents expressed a strong interest, while 55% indicated a general interest in reading Si Ito comics, which are produced from recycled paper and feature comic applications available in the market. The results indicate that Si Ito comics can serve as a medium for promoting tourism in North Sumatra to an international audience. In addition to endorsing eco-friendly initiatives, Si Ito's comic books serve as a vehicle for promoting tourism in North Sumatra through bilingual content, functioning as a learning medium for foreign language acquisition.